Opposites - Boynton, Sandra (New York, N.Y. : Little Simon, 1995)
Takes a child through pairs of opposite words.
On board pages.
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms